Foreign Aid for Development 2010
DOI: 10.1093/acprof:oso/9780199580934.003.0014
|View full text |Cite
|
Sign up to set email alerts
|

14 Aid and Rent‐driven Growth: Mauritania, Kenya, and Mozambique Compared

Abstract: This paper conceptualises foreign aid as a geopolitical form of rent in order to help distinguish the conditions under which aid is detrimental to sustained economic recovery from those where it is beneficial. Foreign aid shares with natural resource rent and contrived (i.e., government monopoly) rent the property of being a large revenue stream that is detached from the economic activity that generates it, and elicits political contests for its capture. Rent-driven models suggest such contests have two advers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2016
2016
2016
2016

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 26 publications
(30 reference statements)
0
2
0
Order By: Relevance
“…Like resource rents, aid revenues can reduce government's dependence on taxes from its own citizens, weakening its accountability to them. Collier (2006) calls aid and resource revenues ''sovereign rents" that generate dysfunctional rent-seeking behavior and tend to receive less scrutiny from legislators and citizens than other revenues (also see Auty, 2007). Fig.…”
Section: Taxation Governance and Sovereign Rentsmentioning
confidence: 99%
“…Like resource rents, aid revenues can reduce government's dependence on taxes from its own citizens, weakening its accountability to them. Collier (2006) calls aid and resource revenues ''sovereign rents" that generate dysfunctional rent-seeking behavior and tend to receive less scrutiny from legislators and citizens than other revenues (also see Auty, 2007). Fig.…”
Section: Taxation Governance and Sovereign Rentsmentioning
confidence: 99%
“…Several studies based on cross-country regressions over large heterogeneous samples of countries have provided a wide range of contradictory results. For instance, Roodman (2008) argued that foreign aid has no effect or barely affects growth; similarly many others such as McKinley (2005), Easterly (2005), Collier (2006), Auty (2007) and Moyo (2009) further argued that aid even undermines growth in recipient countries. On the contrary others such as Sachs (2005), Karras (2006) and Minoiu and Reddy (2006) had suggested that foreign aid has a positive influence on economic growth.…”
Section: Related Literaturementioning
confidence: 99%